Surviving Impostor Syndrome: Navigating Through the Mental Roller coaster of a Doctoral Sojourn - Fitriyah, Siti Masrifatul (Journal of International Students, 2021)
Studying overseas may offer myriad riches of extraordinary experiences, especially due to the opportunities to immerse into a different academic culture. However, for some, the difference may be a hurdle that brings them into a mental roller coaster along with their academic career. In this reflective paper, against the backdrop of my overseas studies experiences, I recount my bumpy journey of battling the so-called impostor syndrome which prevented me from being productive until I found the lights at the end of the tunnel and finally found a way to move on with my journey and earned my degree. Self-appreciation and community support seemed to be the most important influences that may have led me to be free from the syndrome and to finally achieve my main objectives.